Hubungan Antara Fungsi Kognitif Dengan Riwayat Jatuh Pada Lanjut Usia Di Desa Jaten Kecamatan Juwiring Klaten - Damayanti, B. Adelina S.; , Yulisna Mutia Sari, SSt.FT., M.Sc (GRS) (2017)
ABSTRACT Background: Cognitive impairments are common problems that often happen for elders. The difficulties for remembrance function or for expressing verbally or orally are the kinds of decreasing for cognitive function. The decreasing of cognitive function for elders are the main cause of inability for doing normal daily activities and also it is an often causes that make dependence to other people to care dependence for elders. To know the cognitive impairment for elders, it can be measured by using mini mental state examination (MMSE) which has 30 total score. Research purposes: to know the correlation between cognitive function and falling history for elders in Jaten village Juwiring subdistrict Klaten. Research benefit: to be able to know the correlation between cognitive function and falling history for elders in Jaten village Juwiring subdistrict Klaten. Research method: this research is an observational research with cross sectional approach. The sampling technique used is purposive sampling with 65 samples. The measurement of cognitive function uses Mini Mental State Examination (MMSE) by summing up the score in every question whereas the measurement of the fall history uses Wilhan research questionnaire, 2009 by identifying the fall history. The correlation test uses Chi Square test. Research findings: Based on Chi-Square test, it is known that p-value score is 0,013 < 0,005 so H0 is declined and Hα is accepted. It can be interpreted that there is a correlation between cognitive function and falling history for elders in Jaten village Juwiring subdistrict Klaten. Conclusion: There is a correlation between cognitive function and falling history for elders in Jaten village Juwiring subdistrict Klaten. Keywords: Cognitive Function, Fall History, MMSE, Elderly People